Harmony Within the New Digital Paradigm: Management of Human Factors and Balance Between New and Legacy Practices - Calcagno, Camila (Digital Repository of Theses, 2024)
Digitalization has become a central topic within societies and organizations, being described as a new paradigm or as the fourth industrial revolution. This is a change taking place at many layers, including social, economic, private and public layers that is impacting people’s needs, behaviour and expectations. The impact has been so profound that even the markets and industries are shifting, and organizations are finding themselves in extremely fast-changing environments where the competition is greater than ever and where the customers are demanding and behaving in a different way than before. The purpose of this research is to place the management of the reaction of the people involved in change due to digitalization as a central moderating factor that can have a direct positive impact on these processes, being a main enabler. Reactions will be different, depending on many variables such as the people perception, knowledge and understanding but, by placing the management of their reaction at the center and by proactively addressing it, that expected resistance can be brought to significantly lower levels. This thesis aims to show that the human variable is such a central piece in digital transformation processes that the success of them can be directly dependent on it. The research was performed doing a sistematic literature review together with a measurement instrument in the form of a comprehensive survey that was filled by one-hundred and thirty-four respondents across the globe and from many industries. Based on this research, it is important to understand that the environment in which organizations operate is fast and ever-changing. There are constantly new ways of doing things, new technologies and frameworks that could be implemented, new strategies to be explored, etc. What is not different is the need for change with its human centricity. This is just the beginning of this new digital era and there are many more transformational processes coming our way. Regardless of their shape or form, it is critical to be not only relying on traditional pillars such as technology, culture and human resources, but to also include change management practices and human behavior.